Monoclonal antibodies to host cellular receptors for the treatment and prevention of HIV-1 infection. Issue 3 (May 2015) - Pace, Craig; Markowitz, Martin
<x xml:space="preserve">Abstract</x> Purpose of review Clinically relevant monoclonal antibodies (mAb) to host cellular receptors have been generated to both the CD4 receptor and the CCR5 coreceptor, cell surface proteins critical for HIV-1 entry. Ibalizumab is a novel humanized mAb that binds to a conformational epitope on CD4 and blocks entry of HIV-1. It has broad and potent antiviral activity in vitro and in vivo. PRO 140 is a humanized mAb that binds to the CCR5 coreceptor and inhibits CCR5-tropic HIV-1 by interfering with viral entry. Antiviral activity has been demonstrated both in vitro against R5 viruses and in vivo in HIV-1-infected individuals harboring CCR5-tropic virus. Recent findings Both antibodies have been administered intravenously in early-phase clinical trials, and current emphasis is on the development of formulations that can be administered subcutaneously. Most recently, bispecific antibodies combining either ibalizumab or PRO 140 with anti-Env broadly neutralizing antibodies have been constructed with vastly improved in-vitro neutralizing profiles, and may offer substantial advantages in the clinic. Summary mAb to host cellular receptors particularly when combined with broadly neutralizing antibodies in novel conformations may offer advances in both the treatment and prevention of HIV-1 infection.